Effects of sediment bypass tunnels on grain size distribution and benthic habitats in regulated rivers. Issue 4 (2nd October 2017) - Auel, Christian; Kobayashi, Sohei; Takemon, Yasuhiro; Sumi, Tetsuya
ABSTRACT: Four dams in Japan and Switzerland with Sediment Bypass Tunnels (SBT) as a measure against reservoir sedimentation were monitored to analyse the effects of sediment supply on the downstream environment based on up- to downstream differences in geomorphological and biological characteristics. SBT operation times ranged from 93 years at Pfaffensprung and 17 at Asahi to only three years at Solis and no operation at Koshibu. Sediment grain size distribution was monitored, and microhabitats and invertebrates were analysed in terms of richness and composition. Results showed that grain sizes were coarser down- than upstream at dams with newly established SBTs, while they were similar or finer for dams with long SBT operation. Analysis of biotic data revealed that microhabitat and invertebrate richness was low directly below the dam but increased further downstream the longer the SBT operation. Sedentary species dominated at locations where bed conditions were stable, e.g. directly downstream of the dam at Koshibu. Recovery of downstream environment with increasing SBT operation time was disclosed by the Bray–Curtis similarity index, which evaluated an overlap between up- and downstream reaches for both microhabitat composition and invertebrate communities. With increasing operation time, both indices increased, revealing the positive effects of long-term SBT operation.